Analysis on Thermal Environment of Office Room Equipped with Radiant Cooling Workstation. (2017) - Song, Chunhui; Li, Nianping; He, Yingdong; He, De; He, Meiling; Chen, Haowen
Abstract: In this paper, an experiment was designed to compare the thermal environment between the fan coil unit system (Case 2) and the combination of radiant cooling workstation and fan coil unit system (Case 1). Through the numerical simulation software, namely Airpak, the indoor air temperature and velocity were compared in two cases. Compared to Case 2, there are 81.82% and 7.81% decrease in vertical and horizontal temperature difference, respectively. However, the vertical air temperature difference between head and feet is 0.97℃, which is higher than Case 2. Also, the mean air velocity in Case 1 is lower than Case 2, and the air velocity in occupied zone of Case 1 ranges from 0.065 m/s to 0.12 m/s.